Toward a Dynamic Capabilities Framework for Engendering 4IR-Enabled Circular Economy in a University of Technology - Sinxadi, Lindelwa; Ngowi, Alfred Beati; Ramakrishna, Seeram; Awuzie, Bankole (Frontiers in Sustainability, 2021)
Universities are placed in a disadvantaged position as it pertains to the holistic adoption of 4IR technologies and the subsequent deployment thereof in tackling climate change through improved circular economy (CE) performance. Accordingly, the contribution of 4IR technologies in driving effective CE implementation in higher education contexts remain limited. In this study, the need for a dynamic capabilities’ framework for the utilization of the 4IR technologies in enabling CE, is brought to the fore and a framework proposed accordingly. The utility of a dynamic capabilities framework in facilitating the implementation of the CE concept using 4th industrial revolution (4IR) technologies in universities within the context of a South African University of Technology (SAUoT) is highlighted. The proposed framework presents a platform for facilitating the effective adoption and implementation of 4IR technologies in directly improving CE and indirectly, thereby contributing to climate change mitigation. Also, the opportunities and challenges to the deployment of 4IR technologies in driving CE implementation within SAUoT and its host environment was identified. This study holds salient implications for the policy makers, academic leaders, and innovation managers in university ecosystems and local government authorities across South Africa and beyond.